Three-dimensional virtual planning for nodule resection in solid organs: A systematic review and meta-analysis. (September 2021) - Zanon, Matheus; Altmayer, Stephan; Watte, Guilherme; Pacini, Gabriel Sartori; Mohammed, Tan-Lucien; Marchiori, Edson; Pinto Filho, Darcy Ribeiro; Hochhegger, Bruno
Abstract: Objectives: To systematically review the effects of 3D-imaging virtual planning for nodule resection in the following solid organs: lung, liver, and kidney. Methods: MEDLINE, EMBASE, and Cochrane Library were searched through September 31, 2020 to include randomized and non-randomized controlled studies that compared outcomes of surgical resection of lung, liver, or kidney nodule resection with and without 3D virtual planning with computed tomography. From each article, the mean operation time (OT), mean estimated blood loss (EBL), mean postoperative hospital stay (POHS), and the number of postoperative events (POE) were extracted. The effect size (ES) of 3D virtual planning vs. non-3D planning was extracted from each study to calculate the pooled measurements for continuous variables (OT, EBL, POHS). Data were pooled using a random-effects model. Results: The literature search yielded 2397 studies and 10 met the inclusion criteria with a total of 897 patients. There was a significant difference in OT between groups with a moderate ES favoring the 3D group (ES, -0.56; 95%CI: 0.91, -0.29; I 2  = 83.1%; p < .001). Regarding EBL, there was a significant difference between 3D and non-3D with a small ES favoring IGS (ES, -0.18; 95%CI: 0.33, -0.02; I 2  = 22.5%; p = .0236). There was no difference between the 3D and non-3D groups for both POHS (POHS ES, -0.15; 95%CI: 0.39, 0.10; I 2  = 37.0%; p = .174) and POE (POE odds ratio (OR), 0.80; 95%CI:0.54, 1.19; I 2  = 0.0%; p = .0.973). Conclusions: 3D-imaging planning for surgical resection of lung, kidney, and liver nodules could reduce OT and EBL with no effects on immediate POHS and POE. Improvements in these perioperative variables could improve medium and long-term postoperative clinical outcomes. Highlights: 3D-imaging virtual planning for surgical resection of lung, kidney, and liver nodules reduce operation time and perioperative blood loss. 3D-imaging virtual planning did not have any effects on postoperative events or hospital stay. Shorter operation time and blood losses could influence medium and long-term clinical outcomes of solid organs nodule resection.